Is it safe to expand the indications for split liver transplantation in adults? A single‐center analysis of 155 in‐situ splits. Issue 7 (26th April 2022) - Lau, Ngee‐Soon; Ly, Mark; Liu, Ken; Majumdar, Avik; Strasser, Simone I.; Biswas, Raaj K.; McCaughan, Geoffrey W.; Crawford, Michael; Pulitano, Carlo
Abstract: Introduction: Split liver transplantation (SLT) enables two recipients to be transplanted using a single donor liver; typically, an adult and a child. Despite equivalent long‐term outcomes to whole grafts in selected adults, the use of these grafts in high‐risk adult recipients with high model for end‐stage liver disease (MELD) scores (≥30), a poor pre‐transplant clinical status (ICU or hospital‐bound), acute liver failure or retransplantation remains controversial. Methods: We retrospectively analyzed all deceased donor adult liver transplants performed between July 2002 and November 2019 at a single high‐volume center and performed a propensity score‐matched analysis. A subgroup analysis was performed to assess utility of these grafts for high‐risk recipients. Results: A total of 1090 adult liver transplants were performed, including 155 SLT (14%). Graft survival at 1‐, 3‐ and 5‐years were comparable between recipients of split and whole liver grafts (82%, 79% and 74% vs. 86%, 81% and 77%, respectively, log rank P = .537), as was patient survival at 1‐, 3‐ and 5‐years. Recipients of split grafts were more likely to have biliary complications and hepatic artery thrombosis, but equivalent long‐term survival. Recipients with high MELD scores or a poor pre‐transplant clinical status had similar patient and graft survival and complication profiles irrespective of whether they received split or whole grafts. Conclusions: SLT is an important method for addressing donor shortages and provides comparable long‐term outcomes in adult recipients despite an increase in short‐term complications. SLT use in high‐risk recipients should be considered to allow for sickest‐first allocation policies.